Clinicopathologic study of triple-negative breast cancer with special reference to basal-like breast cancer phenotype in a tertiary care hospital of Eastern India - Rajashree Pradhan,; Sajeeb Mondal,; Mrinal Sikdar,; Sankha Chatterjee, (Asian Journal of Medical Sciences, 2023)
Background: Triple-negative breast cancer (TNBC) is defined as absent expression of estrogen receptor (ER) and progesterone receptors and human epidermal growth factor receptors (HER2neu). These cancers are associated with poor prognosis. Aims and Objectives: We aimed at to study the clinicopathological profile and survival among women with TNBC. Materials and Methods: The study was conducted over a period of 4 years. Surgical specimens of patients with breast cancer were analyzed histopathologically as well as immunohistochemical analysis for estrogen, progesterone, HER2neu, and Ki-67 index was also done. Statistical analysis was done using software version 20.0. Results were expressed in number and percentage. Comparison was done by x2 test. P=0.05 was considered statistically significant. Results: In our study, 26.92% cases were of TNBC. Predominant age group affected was between 50 and 70 years. Most common histologic type was invasive carcinoma of no special type with higher grade (Grades 2 and 3) mostly with frequent nodal metastasis. Higher percentage of Ki-67 proliferation index and basal cytokeratin expression were associated with higher tumor grade and stage along with reduced short-term disease-free survival on follow-up. Conclusion: TNBCs are usually of higher grade with frequent recurrences and distant metastasis. There are no widely accepted prognostic markers available. Panel of immunohistochemical markers should be used specially to categorize the basal-like breast cancer subtype among TNBCs for better clinical outcome.